Efektifitas Edukasi “Biasakan Suntik Insulin (Bisul)” terhadap Kemandirian Pasien Diabetes Mellitus dalam Pemberian Insulin di RSU Islam Harapan Anda Kota Tegal - Farah El Yusri; Apriliani Yulianti; Sri Wahyuni (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Diabetes mellitus is a disease caused by inadequate insulin secretion or impaired insulin function. One treatment for DM is insulin administration. To make insulin administration easier and more effective, the "BISUL (Get Used to Injecting Insulin)" education program is provided. This study aims to determine the effectiveness of the "BISUL (Get Used to Injecting Insulin)" education program on increasing the independence of diabetes mellitus patients in administering insulin. Method: This study was a quasi-experimental study with a pretest-posttest design with a control group. The sample size was 56 type 2 diabetes patients, consisting of 28 patients in the intervention group and 28 patients in the control group, obtained through accidental sampling. Data were collected using a checklist based on the insulin injection SAP. Data analysis was performed using the Wilcoxon and Mann-Whitney tests. Results: Before being given education on BISUL in the intervention group, 20 patients (71.4%) were not independent. After being given education, the majority of patients were independent, 24 patients (85.7%). In the control group, most patients were not independent, 19 patients (67.9%), after being given standard hospital care, most patients were not independent (53.6%). There was a difference in the level of independence of type 2 DM patients in administering insulin between the intervention group and the control group p value (0.000). There was a difference in the level of independence of the intervention and control groups with a difference in value of 2.67. Conclusion: There was a difference in the level of independence of type 2 DM patients in administering insulin between the intervention group and the control group p value (0.000). There was a difference in the level of independence of the intervention and control groups with a difference in value of 2.67.